2014
DOI: 10.1039/c4cc07155g
|View full text |Cite|
|
Sign up to set email alerts
|

Efficient delivery of siRNAs by a photothermal approach using plant flavonoid-inspired gold nanoshells

Abstract: Polymer gold nanoshells (PGNs) are prepared by a novel plant-inspired flavonoid surface modification method. The PGNs show dramatic photothermal properties, which can facilitate the endosomal escape and delivery of siRNA into the cytoplasm of cells. Efficient gene silencing has been achieved using siRNA immobilized PGNs, suggesting the potential applications of in vitro gene regulation by an external NIR stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Oxidation with air in Tris buffer is often applied as a dip coating to create PDA films on various types of surfaces, such as Teflon, aluminium oxide, silica, stainless steel, various polymers and nanostructures like carbon nanotubes, magnetic nanoparticles and gold nanoparticles . The thickness of films on the one hand and the size and shape of PDA objects on the other can be influenced by reaction time, concentration, solvent, additives and pH .…”
Section: Polydopamine – Structural and Synthetic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation with air in Tris buffer is often applied as a dip coating to create PDA films on various types of surfaces, such as Teflon, aluminium oxide, silica, stainless steel, various polymers and nanostructures like carbon nanotubes, magnetic nanoparticles and gold nanoparticles . The thickness of films on the one hand and the size and shape of PDA objects on the other can be influenced by reaction time, concentration, solvent, additives and pH .…”
Section: Polydopamine – Structural and Synthetic Aspectsmentioning
confidence: 99%
“…However, monomer coating was assumed through coordination of the amino groups to the surface of the support and exposing unmodified pyrogallyl groups to the environment. Anyway the coating was used for interesting applications such as the ROP of lactide and the formation of gold shells from gold salts in order to obtain composites for gene silencing controlled by near IR radiation …”
Section: Pdanas By Oxidative Polymerization Of Da Derivativesmentioning
confidence: 99%
“…In contrast, after laser irradiation, most of the FAM‐siRNA fluorescence could be seen separated from the LysoTracker signal, suggesting efficient endosomal release. These observations indicate that the micelleplexes escaped from endosomal trafficking to lysosomes, which contributed to the improved siRNA activity …”
Section: Resultsmentioning
confidence: 84%
“…To successfully immobilize primers on the polystyrene (PS) plastic surface, we have coated the microchannels with pyrogallol 2‐aminoethane molecules. It has been reported that a simple coating of pyrogallol 2‐aminoethane on the substrates can generate thiol reactive surfaces for various biomolecule immobilizations . Surface modification and primer immobilization have been verified by X‐ray photoelectron spectroscopy (XPS) analysis and UV–vis spectroscopy (Figure S5, Supporting Information).…”
mentioning
confidence: 92%